SHS Studentsâ Difficulty in Solving Impulsee and Momenyum Problem - Saifullah, A. M.; Sutopo, S.; Wisodo, H. (Jurnal Pendidikan IPA Indonesia, 2017)
Impulse momentum theorem is one of the fundamental principles of physics, especially in mechanics. Therefore, studentsâ understanding of impulse and momentum will contribute to their success in learning physics. This study exposed common students difficulties in solving problems related to impulse and momentum. The subjects consisted of 175 students of a Senior High School in Malang, 70 students of grade XI who recently learned about impulse and momentum and 105 students of grade XII who relearned the topic for national examination preparation. The data were gathered using multiple-choice test with open explanation and confidence rating scale. The study concluded that the studentsâ difficulties were not only caused by their lack understanding of the concepts but also by their deficiency in using vectors.